2021
DOI: 10.1002/term.3178
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a soluble eggshell membrane/agarose composite scaffold with possible applications in cartilage regeneration

Abstract: Articular hyaline cartilage is an extremely hydrated, not vascularized tissue with a low‐cell density. The damage of this tissue can occur after injuries or gradual stress and tears (osteoarthritis), minor damages can be self‐healed in several weeks, but major injuries may eventually require surgery. In fact, in this case, because of nature of the cartilage (the absence of cells and vascularization) it is difficult to expect its natural regeneration in a reasonable amount of time. In recent years, cell therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…The swelling ratio is another essential factor in tissue engineering because it is associated with the degree of water absorption that allows efficient cell‐loading and nutrient delivery 79 . To evaluate their potential as a tissue regeneration material, the swelling capacity of the GelMA/CSMA/HyMA/Eggshell hybrid hydrogel scaffolds was measured in a PBS medium.…”
Section: Resultsmentioning
confidence: 99%
“…The swelling ratio is another essential factor in tissue engineering because it is associated with the degree of water absorption that allows efficient cell‐loading and nutrient delivery 79 . To evaluate their potential as a tissue regeneration material, the swelling capacity of the GelMA/CSMA/HyMA/Eggshell hybrid hydrogel scaffolds was measured in a PBS medium.…”
Section: Resultsmentioning
confidence: 99%
“…Garakani et al [ 76 ] proved that mechanical stimulation is an effective method to enhance cartilage extracellular matrix synthesis, and agarose, which has both biocompatibility and some mechanical strength, has been widely used as a cell culture scaffold for mechanical stimulation studies. When chondrocytes are attached to a scaffold composed of agarose gel, the action of external forces can accelerate the directed differentiation of chondrocytes, while stimulating the proliferation of differentiated chondrocytes and the secretion of ECM [ 77 , 78 ]. Although the applied mechanical load can induce the differentiation of chondrocytes and also promote the synthesis of the extracellular matrix of cartilage tissue, it is not the only factor that affects the synthesis of cartilage matrix; the surface structure of the material that encases the chondrocytes is also crucial.…”
Section: Application and Advantages Of Organic Nanomaterials In Carti...mentioning
confidence: 99%
“…Several studies have used the 3-mercaptopropionic acid-extraction method to develop SEP-containing scaffolds for cartilage, skin, and bone TE. Been et al combined SEPs with agarose to fabricate a scaffold for cartilage repair and regeneration . Compared to pure agarose scaffolds, agarose-SEP scaffolds had faster degradation.…”
Section: Eggshell Membranementioning
confidence: 99%
“…[144][145][146][147] SEPs with agarose to fabricate a scaffold for cartilage repair and regeneration. 144 Compared to pure agarose scaffolds, agarose-SEP scaffolds had faster degradation. In vitro studies with rabbitderived chondrocytes showed that the incorporation of SEPs into the scaffold increased cell proliferation and survival, resulting in higher chondrogenic gene expression and increased synthesis and deposition of ECM proteins.…”
Section: Eggshell Membranementioning
confidence: 99%